Համընդհանուր ցանցային լեզու - Փարեմուզյան, Լիլիթ («Նաիրի» հրատ.)
UNL- is a computational universal artificial network language which aims at description, preservation and dissemination of global information, from any natural language, regardless of the form of the computer environment. The works of the Armenian module began in 2001. There have been done works on a creation of the formal description of Armenian language, the automatic processing of text, the creation of automatic dictionaries and computer data bases.
Keywords: Ծրագրավորման լեզուներ